Gambaran Karakteristik Pasien Infeksi Oportunistik Tuberkulosis dengan HIV/AIDS di RSUD Al-Ihsan - Adinda Riany Putri Sundari; Alya Tursina; Tita Barriah Siddiq (UNISBA Press, 2023)
Abstract. Data from the World Health Organization (WHO) for 2021 shows that 36.3 million people live with the Human Immunodeficiency Virus / Acquired Immunodeficiency Syndrome (HIV/AIDS). One province that has made a major contribution to HIV/AIDS cases is West Java, with 6,066 HIV cases and 313 AIDS cases. Data on cases of people living with HIV/AIDS (ODHA) in the city of Bandung until June 2021 found a total of 5,741 cases. Tuberculosis is the most common opportunistic infection that occurs in HIV/AIDS patients. A low immune system can exacerbate both diseases. This study aims to determine the characteristics of opportunistic tuberculosis infection patients with HIV/AIDS at Al-Ihsan Hospital for the 2017-2021 period. The sampling technique used total sampling, with the subject being 62 medical records of HIV/AIDS patients with tuberculosis at Al-Ihsan Hospital. Descriptive research with a cross-sectional approach. The results of this study showed that the number of HIV/AIDS patients with tuberculosis for the 2017-2021 period at Al-Ihsan Hospital was 62 people, out of the total the majority were male, namely 46 people (74%), aged early adulthood (26- 35 years old), 25 people (40%), last high school education, 42 people (68%), 50 people (81%) had pulmonary tuberculosis, 51 people (82%) had a CD4 count <200 cells/μL, and the most commonly experienced clinical symptoms were fatigue by 73% and weight loss by 73%. Characteristics of patients with opportunistic tuberculosis infections with HIV/AIDS at Al-Ihsan Hospital are dominated by men, aged early adulthood, last high school education, have pulmonary tuberculosis, with CD4 counts <200 cells/µL and clinical symptoms of fatigue and weight loss. Keywords: Opportunistic infections, Tuberculosis, TB-HIV co-infection Abstrak. Data World Health Organization (WHO) 2021, diestimasikan 36,3 juta orang hidup dengan Human Immunodeficiency Virus / Acquired Immunodeficiency Syndrome (HIV/AIDS). Salah satu provinsi yang berkontribusi besar pada kasus HIV/AIDS adalah Jawa Barat, sebanyak 6.066 kasus HIV dan 313 kasus AIDS. Data kasus orang hidup dengan HIV/AIDS (ODHA) di Kota Bandung sampai bulan Juni 2021 ditemukan sebanyak 5.741 kasus. Tuberkulosis merupakan infeksi oportunistik paling umum yang terjadi pada pasien HIV/AIDS. Rendahnya sistem kekebalan tubuh dapat memperburuk keadaan kedua penyakit tersebut. Penelitian ini bertujuan untuk mengetahui karakteristik pasien infeksi oportunistik tuberkulosis dengan HIV/AIDS di RSUD Al-Ihsan periode 2017-2021. Teknik pengambilan sampel menggunakan total sampling, dengan subjek 62 data rekam medis pasien HIV/AIDS disertai penyakit tuberkulosis di RSUD Al-Ihsan. Penelitian deskriptif dengan pendekatan potong lintang. Hasil penelitian ini menunjukan jumlah pasien HIV/AIDS dengan penyakit tuberkulosis periode 2017-2021 di RSUD Al-Ihsan sebanyak 62 orang, dari total keseluruhan sebagian besar berjenis kelamin laki-laki yaitu sebanyak 46 orang (74%), berusia dewasa awal (26-35 tahun) yaitu sebanyak 25 orang (40%), pendidikan terakhir SLTA yaitu sebanyak 42 orang (68%), sebanyak 50 orang (81%) mengalami tuberkulosis paru, sebanyak 51 orang (82%) memiliki jumlah CD4 <200 sel/μL, dan gejala klinis yang paling banyak dialami adalah mudah lelah sebanyak 73% dan penurunan berat badan sebanyak 73%. Karakteristik pasien infeksi oportunistik tuberkulosis dengan HIV/AIDS di RSUD Al-Ihsan didominasi oleh laki-laki, berusia dewasa awal, pendidikan terakhir SLTA, mengalami tuberkulosis paru, dengan jumlah CD4 <200 sel/μL dan gejala klinis mudah lelah sebanyak dan berat badan turun. Kata Kunci: Infeksi oportunistik, Tuberkulosis, Koinfeksi TB-HIV